Diet‐induced obesity, adipose inflammation, and metabolic dysfunction correlating with PAR2 expression are attenuated by PAR2 antagonism. Issue 12 (20th August 2013) - Lim, Junxian; Iyer, Abishek; Liu, Ligong; Suen, Jacky Y.; Lohman, Rink‐Jan; Seow, Vernon; Yau, Mei‐Kwan; Brown, Lindsay; Fairlie, David P.
Abstract : Excessive uptake of fatty acids and glucose by adipose tissue triggers adipocyte dysfunction and infiltration of immune cells. Altered metabolic homeostasis in adipose tissue promotes insulin resistance, type 2 diabetes, hypertension, and cardiovascular disease. Inflammatory and metabolic processes are mediated by certain proteolytic enzymes that share a common cellular target, protease‐activated receptor 2 (PAR2). This study showed that human and rat obesity correlated in vivo with increased expression of PAR2 in adipose tissue, primarily in stromal vascular cells (SVCs) including macrophages. PAR2 was expressed more than other PARs on human macrophages and was increased by dietary fatty acids (palmitic, stearic, and myristic). A novel PAR2 antagonist, GB88 (5‐isoxazoyl‐Cha‐Ile‐spiroindene‐1, 4‐piperidine), given orally at 10 mg/kg/d (wk 8–16) reduced body weight by ~10% in obese rats fed a high‐carbohydrate high‐fat (HCHF) diet for 16 wk, and strongly attenuated adiposity, adipose tissue inflammation, infiltrated macrophages and mast cells, insulin resistance, and cardiac fibrosis and remodeling; while reversing liver and pancreatic dysfunction and normalizing secretion of PAR2‐directed glucose‐stimulated insulin secretion in MIN6 β cells. In summary, PAR2 is a new biomarker for obesity, and its expression is stimulated by dietary fatty acids; PAR2 is a substantial contributor to inflammatory and metabolic dysfunction; and a PAR2 antagonist inhibits diet‐induced obesity and inflammatory, metabolic, and cardiovascular dysfunction.—Lim, J., Iyer A., Liu, L., Suen J. Y., Lohman R.‐J., Seow V., Yau M.‐K., Brown, L., Fairlie, D. P., Diet‐induced obesity, adipose inflammation, and metabolic dysfunction correlating with PAR2 expression are attenuated by PAR2 antagonism. FASEB J. 27, 4757–4767 (2013). www.fasebj.org